Directed Technical Change and Energy Intensity Dynamics: Structural Change vs. Energy Efficiency - Karol Kempa; Christian Haas (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper uses a theoretical model with Directed Technical Change to analyse the observed heterogeneous energy intensity developments. Based on the empirical evidence on the underlying drivers of energy intensity developments, we decompose changes in aggregate energy intensity into structural changes in the economy (Sector Effect) and within-sector energy efficiency improvements (Efficiency Effect). We analyse how energy price growth and the relative productivity of both sectors affect the direction of research and hence the relative importance of the aforementioned two effects. The relative importance of these effects is determined by energy price growth and relative sector productivity that drive the direction of research. In economies that are relatively more advanced in sectors with low energy intensities, the Sector Effect dominates energy intensity dynamics given no or moderate energy price growth. In contrast, the Efficiency Effect dominates energy intensity developments in economies with a high relative technological level within their energy-intensive industries if moderate energy price growth is above a certain threshold. We further show that temporal energy price shocks might induce a permanent redirection of innovation activities towards sectors with low-energy intensities.
Keywords: O33; Q43; Q55; 330